Effective Inculturation and Ethnic Identity - Aymes, María de la Cruz ((InCulturation. Working Papers on Living Faith and Cultures ;, 1987)
Contiene varios ensayos de antropología y religión sobre el tema de inculturación e identidad étnica. Artículos y autores: "CaseStudy: Catechesis of Hispanic in the United States Today" por María de la Cruz Aymes y Francis J. Buckley; Kinship in the Trinity" por Charles Nyamiti; "Symbol and Root Paradigm: The Locus of Effective Inculturation" por W.E. Biernatzki; "Inculturation as Communication" por George A. de Napoli; "Inculturation of Transculturation Among the por Eugene Mauer.